Molecular identification of some earthworm species (Annelida; Oligochaeta) In Kurdistan-Iraq - Hawre Husamulddin Othman; Sherwan Taeb Ahmad (Zanco Journal of Pure and Applied Sciences, 2020)
A total of 256 specimens of earthworms were collected from four provinces in Kurdistan region of Iraq includes Erbil, Sulaymaniyah, Duhok and Halabja, during a period from July 2018 to April 2019. DNA barcoding was used for the first time in Iraq for identification of earthworms to species level. A modified CTAB method was used for isolation and extraction of DNA. Mitochondrial COI region was amplified and sequenced to determine the differences among species. Results revealed that six species belong to three genera of two families; Lumbricidae and Megascolecidae were successfully identified and the similarity of all species was 95% or more. which are Amynthas morissi (Beddard, 1892) ; A. luridus (Shen et al., 2019) ; A. gracilis (Kinberg, 1867) ; Aporrectodea trapezoids (Duges, 1828) ; A. longa (Ude, 1888) ; and Healyella syriaca (Rosa, 1893). Depending on the present results the species (Haelyella syriaca, Amynthas gracilis and Amynthas luridus) are considered as new records to Iraqi fauna. The phylogenetic tree analysis using maximum likelihood programs shown that there are seven clades. This study could be a suitable research program for future studies on the earthworms in Iraq.